Policy Analysis: Food Security in Malaysia / Faridah Suffian and Firdausi Suffian - Suffian, Faridah; Suffian, Firdausi (2021)
Malaysia is generally food secure in the Global Food Security Index report 2020 which ranked 43rd out of 113 other countries globally (Global Food Security Index, n.d.). Malaysia has achieved relatively impressive growth over recent decades with the agricultural sector making a major contribution to this growth. The agriculture industry has been the backbone of the Malaysian economy for decades, the development of industrial crop commodities such as rubber, oil palm, and cocoa has been a major contributor to its economic growth. Despite these achievements, the agro-food sector has been considerably left behind in comparison to its commodities crop sector (World Bank, 2020). The country's food sector has remained slow to develop, as illustrated by food trade deficits of RM17 million in 2019 (Ministry of Agriculture and Food Industries Malaysia, 2020). It also depends on imported inputs such as feed, fertiliser, agricultural machinery, and labour, and overall productivity remains low, as the food sector in Malaysia is largely driven by its policy formulation, then and now (Fatimah, 2017). Malaysia's agriculture policies have been prioritizing industrial commodities over the food crop industry as it gives a higher return to the economy over the past decades. Thus, it has marginalised the agro-food sector and has resulted in the agro-food industry being left behind in terms of growth and productivity. Domestic food production is inadequate to meet the country's population's need for food. As a result, import substitution is the most straightforward solution to this problem. Food imports are available since supply is assured and comes from many producing nations such as China, India, Vietnam, Myanmar, and Thailand (Fatimah, 2020). For that reason, the imports of food products have increased year after year, thus restricting the growth of agro-food sectors and indirectly does not drive the national food sector to carry out reforms (Fatimah, 2020). Malaysia's food import bills rise dramatically from RM34 billion in 2011 to RM51 billion in 2019, pointing to increased dependency on food purchases (Ministry of Agriculture and Food Industries Malaysia, 2016, 2020).